Proteomic analysis of plastids the endosperm of developing seeds of Jatropha (Jatropha curcas L.) - Camila Barbosa Pinheiro Jereissati (2015)
Jatropha curcas L. is a plant native to America and belongs to the Euphorbiaceae family. Currently it is gaining economical interest mainly because it is an oilseed crop with potential to produce biodiesel. However, presence of phorbol esters (a class of diterpenes) that are the major toxic constituents of the seeds, limits a better usage of the plant, by making the use of the residue, obtained after the oil extraction from the seeds, unfeasible for animal feed, due to its pro-carcinogenic activity and inflammatory action. Proteomic analysis of the plastids isolated from developing seeds of Jatropha is important because the synthesis of fatty acid as well as phorbol esters, the two most attractive compounds in the study of Jatropha curcas, occur in plastids. Proteomic analysis of this organelle is crucial to better understand and explore not only the biosynthetic pathway of these two compounds but other metabolic pathways , and addtionaly providing foundation for researchs that aimed to develope genotypes with more suitable characteristics for industrial applications. In this study, we performed a proteomic analysis of plastids isolated from the endosperm of developing Jatropha curcas seeds that were in the initial stage of deposition of protein and lipid reserves. Proteins extracted from the plastids were digested with trypsin, and the peptides were applied to an EASY-nano LC system coupled online to an ESI-LTQ-Orbitrap Velos mass spectrometer, and this led to the identification of 1103 proteins representing 804 protein groups, of which 923 were considered as true identifications, and this considerably expands the repertoire of J. curcas proteins identified so far. Of the identified proteins, only five are encoded in the plastid genome, and none of them are involved in photosynthesis, evidentiating the nonphotosynthetic nature of the isolated plastids. Homologues for 824 out of 923 identified proteins were present in three different plastids proteins databases i.e. PPDB, SUBA and PlProt, while homologues for 13 proteins were not found in any of these three databases but were marked as plastidial by at least one of the three prediction programs used (TargetP, ChloroP and PlantMPloc). Functional classification showed that proteins belonging to amino acids metabolism comprise the main functional class, followed by carbohydrate, energy, and lipid metabolisms. The small and large subunits of Rubisco were identified, and their presence in plastids is considered to be an adaptive feature counterbalancing for the loss of one-third of the carbon as CO2 as a result of the conversion of carbohydrate to oil through glycolysis. While several enzymes involved in the biosynthesis of several precursors of diterpenoids were identified, we were unable to identify any terpene synthase/cyclase, which suggests that the plastids isolated from the endosperm of developing seeds do not synthesize phorbol esters. In conclusion, this study provides insights into the major biosynthetic pathways and certain unique features of the plastids from the endosperm of developing seeds at the whole proteome level.